(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Proper Choose of modulation scheme in Free Space Optical (FSO) technique helps to improve FSO performance and this in turn helps to increase FSO link, so in this paper, the modulation schemes Return-to-Zero (RZ), Non Return-to-Zero (NRZ), Differential Phase-Shift Keying (DPSK) and Minimum Shift Keying (MSK) were compared under Bit Error Rate (BER) constrains. Firstly, for Single Input Single Output (SISO) – FSO link and then for 4*4 Multiple Input Multiple Output (MIMO) – FSO link, where both were set up in OptiSystem V.7 simulation, all at the very clear air, clear air, light haze and thin fog conditions. The results concluded that performance of NRZ-OOK was asymptotic to the performance of DPSK in SISO FSO and 4*4 MIMO-FSO, under very clear air, clear air, light haze and thin fog conditions.